Catch as cat can eaudiobook - Brown, Rita Mae (Mrs. Murphy Mystery, 2002)
Never have two species co-created a work of such suspense and humorous catitude as the wildly popular mystery series by Rita Mae Brown and Sneaky Pie Brown. This time out, that agile-witted tiger puss Mrs. Murphy makes the round of parties where Virginia's Very Best People mingle with some of the worst. Together, she and her human must unravel a veritable cat's cradle of ambition, greed, and murder at the center of which waits a killer with the most tangled of motives.